2021
DOI: 10.1155/2021/8893940
|View full text |Cite
|
Sign up to set email alerts
|

Using Particle Swarm Optimization Algorithm to Calibrate the Term Structure Model

Abstract: One of the advantages of stochastic differential equations (SDE) is that they can follow a variety of different trends so that they can establish complex dynamic systems in the economic and financial fields. Although some estimation methods have been proposed to identify the unknown parameters in virtue of the results in the SDE model to speed up the process, these solutions only focus on using explicit approach to solve SDEs, and therefore they are not reliable to deal with data source merged being large and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Many researchers have looked at credit risk assessment and assessment models using a variety of techniques. Zhou et al and Lowd and Davis [6,7] suggested a particle swarm optimization algorithm-based financial credit risk assessment technique. e study in [8] provided an xgbfs-based financial credit risk assessment approach that decreases the dimension of the user's credit data, trains the xgboost assessment model, and then analyses the user's credit risk.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have looked at credit risk assessment and assessment models using a variety of techniques. Zhou et al and Lowd and Davis [6,7] suggested a particle swarm optimization algorithm-based financial credit risk assessment technique. e study in [8] provided an xgbfs-based financial credit risk assessment approach that decreases the dimension of the user's credit data, trains the xgboost assessment model, and then analyses the user's credit risk.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, the process is a suitable noise for financial models, when interest rate amounts increase. Besides, to make a more effective model, researchers use different methods to calibrate models' parameters by considering the real data market [8][9][10][11][12]. e maximum likelihood estimation (MLE) is a famous method to calibrate the model's parameters.…”
Section: Introductionmentioning
confidence: 99%